Mafic dykes intrusive into Pre-Cambrian rocks of the São Luís cratonic fragment and Gurupi Belt (Parnaíba Province), north-northeastern Brazil: Geochemistry, Sr-Nd-Pb-O isotopes, 40Ar/39Ar geochronology, and relationships to CAMP magmatism - Klein, E.L.; Angélica, R.S.; Jourdan, Fred; Babinski, M.; Harris, C. (Elsevier BV, 2013)
Dykes of diabase and microgabbro intruded into Pre-Cambrian rocks of the São Luís cratonic fragment and Gurupi Belt, which are tectonic and erosive windows of the Parnaíba Basin in north–northeastern Brazil. Ar–Ar ages were determined, and major, trace element, and Nd–Sr–Pb–O isotopic compositions of these dykes were measured to provide insights into their age, and into the nature of their mantle sources and petrogenetic processes. The data have also been used to compare the chemical and isotopic signatures of the dykes with those of the Central Atlantic Magmatic Province (CAMP). Four chemical groups of mafic dykes have been identified. These comprise two subtypes of high-Ti rocks (i) HTi-1 (TiO2 < 2.3 wt.%; SiO2 > 47 wt.%), (ii) HTi-2 (TiO2 > 2.7 wt.%; SiO2 > 47 wt.%), in addition to (iii) evolved high-Ti (TiO2 > 4 wt.%; SiO2 of ~ 46 wt.%) and (iv) low-Si (TiO2 > 2.2 wt.%; SiO2 < 45 wt.%) rocks. 40Ar/39Ar geochronology of plagioclase returned ages of 201 ± 4 Ma and 193 ± 10 Ma for the HTi-2 subtype, and of 201 ± 2 Ma and 207 ± 9 Ma for the evolved high-Ti group. The HTi-1 and low-Si groups presented highly disturbed age spectra, and did not allow the definition of their emplacement ages. The Argon data indicate an age > 200 Ma for the low-Si group and are dubious with respect to the age of theHTi-1 subtype, if coeval with (i.e., ~ 200 Ma), or older than, the HTi-2 and evolved high-Ti types.All groups present δ18O values of pyroxene that are compatible with uncontaminated mantle-derived magmas. The HTi-1 subtype (average 143Nd/144Nd200 = 0.512644; 87Sr/86Sr200 = 0.7035; 206Pb/204Pb of 17.86) shows the less enriched and less fractionated (more primitive) trace element distribution of all groups. The HTi-2 subtype shows enriched trace element pattern and depleted Nd–Sr signature (143Nd/144Nd200 = 0.512610; 87Sr/86Sr200 = 0.7037) and average 206Pb/204Pb ratios of 17.23. The evolved high-Ti chemical group shows average ratios of 143Nd/144Nd200 = 0.512558, 87Sr/86Sr200 = 0.7035, and 206Pb/204Pb of 16.88, and the more enriched trace-elements signature among the four groups. The chemical and isotopic compositions and trends of the HTi-1/HTi-2/EHTi types are consistent with their derivation from an asthenosphere-derived parental magma further modified by differentiation and minimal crust contamination (higher in the HTi-2 and EHTi types), and by the derivation of one type from another via fractional crystallization. These high- and evolved high-TiO2 types show ages and some chemical and isotopic features that are consistent with those of the CAMP magmatism. Some differences found are ascribed to petrogenetic processes, such as magma differentiation.A combination of warming of the mantle and edge-driven convection beneath the Pangea supercontinent after the closure of the Neoproterozoic (Brasiliano/Pan-African) orogenies in the Ediacaran–Cambrian boundary might have triggered the magmatic event. The low-Si type shows paired Ta–Nb and Zr–Hf depletions, and depleted Sr–Nd (average 143Nd/144Nd200 = 0.512687; 87Sr/86Sr200 = 0.703) and enriched Pb (206Pb/204Pb of 18.66) isotopic compositions that may be interpreted to result either from interaction of a subcontinental lithospheric mantle with products of an earlier subduction or by contamination of the mantle-derived magma during ascent and emplacement in the continental crust. It is hypothesized that these dykes were emplaced in the Ediacaran–Cambrian boundary, after the Neoproterozoic orogeny that built up the Gurupi Belt and in the early extensional stages that preceded the formation of the Parnaíba Basin.